2008
DOI: 10.1590/s0101-20612008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Soja transgênica BRS 243 RR: determinação de macronutrientes e das isoflavonas daidzeína e genisteína por Cromatografia Líquida de Alta Eficiência (CLAE)

Abstract: The objective of this work was to evaluate the proximate composition, as well as Daidzein (D) and Genistein (G) contents by HPLC, of BRS 243 RR soybean. Sample preparation for the chromatographic analysis involved the use of hexane to remove lipids. Isoflavones were extracted with 70% ethanol containing 0.1% acetic acid. The optimized chromatographic conditions were: C 18 column, mobile phase methanol:5% acetic acid (1:1 v/v), flow rate 0.5 mL/minute, column temperature 30 °C, UV absorbance at 254 nm and volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(29 reference statements)
1
2
0
2
Order By: Relevance
“…In this sense, the increase of the hydrogel doses promoted a greater retention of water for the plant, resulting in the reduction of the protein content. Despite this decrease, the average found in this study (33.08%) is near to the average found by other studies as in treatment with different desiccants (Lacerda et al 2003), different cultivars and crop sites (Minuzzi et al 2009), in selected cultivars with high iron content (Yamada et al 2003), the comparison between conventional and transgenic soybean plants (Ciabotti et al 2006, Alezandro et al 2008, evidenced the hydrogel's potential to maintain the yield of the soybean crop cultivated under deficit without losing biochemical quality, which is of extreme importance, since it is possible to put in the market more quantity of food.…”
Section: Figure 2 Variation Of the Starch Content As A Function Of Tsupporting
confidence: 47%
See 1 more Smart Citation
“…In this sense, the increase of the hydrogel doses promoted a greater retention of water for the plant, resulting in the reduction of the protein content. Despite this decrease, the average found in this study (33.08%) is near to the average found by other studies as in treatment with different desiccants (Lacerda et al 2003), different cultivars and crop sites (Minuzzi et al 2009), in selected cultivars with high iron content (Yamada et al 2003), the comparison between conventional and transgenic soybean plants (Ciabotti et al 2006, Alezandro et al 2008, evidenced the hydrogel's potential to maintain the yield of the soybean crop cultivated under deficit without losing biochemical quality, which is of extreme importance, since it is possible to put in the market more quantity of food.…”
Section: Figure 2 Variation Of the Starch Content As A Function Of Tsupporting
confidence: 47%
“…However, the plants that received treatment with the Hydroplan source did not present significant differences between doses. The carbohydrates in soybean grains are generally quantified indirectly, and therefore, the variation described in the literature is wide ranging from 17% in studies comparing the carbohydrate content in grains and their derivatives (Silva et al 2006) to 35% in studies comparing conventional and transgenic soybeans (Alezandro et al 2008). In this study, about 10% of soluble carbohydrates were found, which is close to 8% described by Oliveira et al (2010) which used most expensive methodologies to quantify the soluble carbohydrate content of different soybean cultivars destined for human consumption.…”
Section: Figure 1 Variation Of Oil (A) Soluble Carbohydrates (B) Anmentioning
confidence: 48%
“…The chemical composition of soybeans can vary with the climate, soil type, geographic location, varieties and agronomic practices, among other factors, and the derivatives of soy products, such as soy extract, also undergo changes in their mineral content. Despite this susceptibility to change, soy and its derivatives are important sources of minerals such as potassium (K), iron da Silva et al 1269 (Fe) and calcium (Ca), highlighting the very high K content (Alezandro et al, 2008). In this context, the present study was conducted to evaluate the chemical characteristics of color and the level of calcium, iron, sodium, potassium and folates in goat's milk-based yogurts with added water-soluble soybean extract (WSSE) and probiotic culture during refrigerated storage.…”
Section: Introductionmentioning
confidence: 99%
“…As isoflavonas livres sem a molécula de açúcar, denominadas agliconas, são consideradas mais importantes presentes na soja. Entre elas, a daidzeína e a genisteína têm se destacado em virtude do seu maior potencial protetor à saúde humana (ALEZANDRO et al, 2008).…”
Section: Características Biológicas Dos Grãosunclassified